Marfan syndrome and pregnancy: maternal and neonatal outcomes. (13th January 2014) - Curry, RA; Gelson, E; Swan, L; Dob, D; Babu‐Narayan, SV; Gatzoulis, MA; Steer, PJ; Johnson, MR
<x xml:space="preserve">Abstract</x> Objective To report outcomes in a recent series of pregnancies in women with Marfan syndrome (MFS). Design Retrospective case note review. Setting Tertiary referral unit (Chelsea and Westminster and Royal Brompton Hospitals). Sample Twenty‐nine pregnancies in 21 women with MFS between 1995 and 2010. Methods Multidisciplinary review of case records. Main outcome measures Maternal and neonatal mortality and morbidity of patients with MFS and healthy controls. Results There were no maternal deaths. Significant cardiac complications occurred in five pregnancies (17%): one woman experienced a type–A aortic dissection; two women required cardiac surgery within 6 months of delivery; and a further two women developed impaired left ventricular function during the pregnancy. Women with MFS were also more likely to have obstetric complications (OR 3.29, 95% CI 1.30–8.34), the most frequent of which was postpartum haemorrhage (OR 8.46, 95% CI 2.52–28.38). There were no perinatal deaths, although babies born to mothers with MFS were delivered significantly earlier than those born to the control group (median 39 versus 40 weeks of gestation, Mann–Whitney U–test, P = 0.04). These babies were also significantly more likely to be small for gestational age (24% in the MFS group versus 6% in the controls; OR 4.95, 95% CI 1.58–15.55). Conclusions Pregnancy in women with MFS continues to be associated with significant rates of maternal, fetal, and neonatal complications. Effective pre‐pregnancy counselling and meticulous surveillance during pregnancy, delivery, and the puerperium by an experienced multidisciplinary team are warranted for women with MFS.